Using SPSS syntax a beginner's guide - Collier, Jacqueline. (SAGE, 2009)
SPSS syntax is the command language used by SPSS to carry out all of its commands and functions. In this book, Jacqueline Collier introduces the use of syntax to those who have not used it before, or who are taking their first steps in using syntax.